Posters 2021
DOI: 10.1136/gutjnl-2020-bsgcampus.296
|View full text |Cite
|
Sign up to set email alerts
|

P221 Non-cirrhotic vs Cirrhotic HCC: comparison between patient characteristics, aetiology and outcomes

Abstract: 6% rivaroxaban. Duration of anticoagulation could be ascertained in 28 patients: 43% had 6 months, 39% lifelong, 7% had 4 months and the other 3 cases separately had 6 weeks, 2 months and 12 months.Of the 51 patients who survived >6 months after diagnosis 59% had repeat CT imaging. The majority (n=23) were anticoagulated and there was recanalisation in 61%, partial recanalisation in 13% and cavernous transformation in 26%. 83% of those with cavernous transformation had portal hypertension.6 of the non-anticoag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…13 Non-cirrhotic HCC patients were older at diagnosis as compared to cirrhotic HCC but had a similar male to female ratio. A similar nding in demographic pro le was observed by Tham et al 14 Of all HCC patients in our study, non-cirrhotic HCC accounted for 27.9%, while the remainder had a background of cirrhosis. In various other studies done worldwide, cirrhosis was reported in 60-99% of patients with HCC.…”
Section: Discussionsupporting
confidence: 90%
“…13 Non-cirrhotic HCC patients were older at diagnosis as compared to cirrhotic HCC but had a similar male to female ratio. A similar nding in demographic pro le was observed by Tham et al 14 Of all HCC patients in our study, non-cirrhotic HCC accounted for 27.9%, while the remainder had a background of cirrhosis. In various other studies done worldwide, cirrhosis was reported in 60-99% of patients with HCC.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of cirrhosis was notably higher (90.8%) in the present study compared with 55% in the EACH study. Cirrhosis is a pivotal factor affecting the survival of patients with HCC [20][21][22], with decompensated cirrhosis contributing to poorer prognosis, owing to both cirrhosis itself and decreased chemotherapy tolerability among these patients [23,24]. Furthermore, the rates of CTP B (26.3%) and ascites (10.5%) were higher in the present study compared with the EACH study (11.0% and 3.3%, respectively), further highlighting the increased risk of decompensated cirrhosis in our patient cohort.…”
mentioning
confidence: 99%